PHARMACOGNOSTIC STANDARDIZATION OF STEMS OF VANDA ROXBURGHII ROXB. - Mukhtar, Hayat M; Kalsi, Vandna (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â  Â Objective: There is an expanding demand of herbal medicines due to their compelling and more secure method for treating different diseases. In the present situation, these drugs are much productive for the treatment of different issues as they have negligible reactions in contrast with the allopathic pharmaceuticals. Vanda roxburghii is an epiphytic plant that finds a mention in the indigenous systems of medicines such as Ayurveda and Unani and has been used traditionally in Bangladesh. In the present investigation, various pharmacognostic standards have been investigated to prove the authenticity of the plant for the claimed traditional uses. Methods: The powdered drug was used for estimating the loss on drying, volatile oil content, ash values, fluorescence studies, extractive values, and phytochemical screening. Macroscopic and microscopic studies were also conducted on the powdered drug. Results: Phytochemical screening has shown the presence of various phytoconstituents such as glycosides, alkaloids, polyphenols, tannins, steroids, flavonoids, resins, and carbohydrates. Conclusion: V. roxburghii has been found to be useful as aphrodisiac, antibacterial, antifungal, antiulcer, anticonvulsant, and antioxidant agent. The present study provides the information on pharmacognostic characteristics, phytochemical screening, and physicochemical parameters.